Design and Application of Spiral Bevel Gear Chamfering Tool based on Kimos - Jingcai Li; Junfang Ma; Wenli Xu; Jia Man (Jixie chuandong)
When the special chamfering machine is widely used to chamfering currently chamfer the end face of spiral bevel gears in the domestic， the adjustment of the grinding wheel is complex， the preparation time is long and the precision is difficult to guarantee. A machining process by using the special chamfering tool to control the movement of the cutter along the designed tooth profile trajectory on a milling machine is proposed， the quality of the chamfering can be ensured， and the material handling is not needed， the personnel is saved. Based on the Kimos software， the design of this kind of tool and the chamfering processing are carried out， and a concrete design example is given.